Surgical Treatment of Solid Pseudopapillary Tumor in Pediatric Patients: Two Case Reports and a Brief Narrative Review - Dario Talloa; Simona Cordaro; Giorgio Attinà; Stefano Mastrangelo; Alberto Romano; Anna Fregola; Palma Maurizi; Lorenzo Nanni; Antonio Ruggiero (Case Reports in Oncological Medicine)
Solid pseudopapillary neoplasms (SPNs) represent a tumor of the exocrine pancreas, belonging to the group of pancreatic cystic neoplasms. It is exceedingly uncommon for SPNs to manifest in extrapancreatic locations, such as the mesocolon, greater omentum, jejunum, and ovary. SPNs are considered very rare, constituting about 0.17%–2.5% of all pancreatic neoplasms and 6% of cystic pancreatic neoplasms. We present two pediatric cases of SPNs: one involving a 16-year-old female patient and the other a 14-year-old girl, both diagnosed and treated in our center with surgical resection. The experience of our center confirms that wide margin surgery, with associated metastasectomy if necessary, represents the therapy of choice for SPNs, ensuring effective control of the disease.